Web-Based System Inventory at PT Sapta Tunas Teknologi - Saputra, Nicholas; Mulyawan, Bagus (International Journal Software Engineering and Computer Science (IJSECS), 2023)
An Information System is a complex framework comprising multiple components that interact harmoniously to gather, store, process, produce, and disseminate valuable information, thereby facilitating and enhancing the operational efficiency of a company's business processes. For technology-driven enterprises like PT Sapta Tunas Teknologi, the implementation of an efficient and integrated inventory information system serves as a pivotal asset. Currently, PT Sapta Tunas Teknologi faces challenges in asset management, including difficulties in stock monitoring, scheduling demonstrations, and maintaining the status of demo devices such as servers, storage units, and switches. The management of demo devices has been predominantly reliant on Google Spreadsheets distributed via the WhatsApp application. This research endeavors to design and deploy a web-based inventory information system, with the primary objective of augmenting the effectiveness of demo device management at PT Sapta Tunas Teknologi. The system's design adheres to the System Development Life Cycle (SDLC) Waterfall methodology, employing a blend of programming languages such as HTML, PHP, Javascript, and the Laravel Framework, while the user interface is enriched by the Bootstrap Framework. The underlying data management system is facilitated by a MySQL database, ensuring robust and efficient data handling.